Enhancing Students’ Mathematical Literacy Skills through Contextual Teaching and Learning (CTL) and Problem Based Learning (PBL) Approaches - Junianto, Junianto; Fonda, Aulia; Firdaus, Muh Wildanul; Ramadhan, Katon Agung (Jurnal Pendidikan Matematika Universitas Lampung, 2025)
The results of the PISA survey conducted by the OECD serve as one of the indicators that the mathematical literacy skills of Indonesian students remain low. Ranking 66th out of 81 countries also indicates that Indonesia is still lagging behind other nations. The purpose of this study is to improve students’ mathematical literacy skills through two alternative learning approaches: Contextual Teaching and Learning (CTL) and Problem-Based Learning (PBL). The research method used was a quasi-experimental design with a pretest-posttest approach to collect data. The population consisted of a junior high school in Yogyakarta, with a sample of two eighth-grade classes. The research instrument was a mathematical literacy test based on PISA-type questions.  The findings indicated that the CTL and PBL approaches were both successful in enhancing students’ mathematical literacy skills. Further analysis through a comparative effectiveness test revealed that the CTL approach was superior to PBL. It is hoped that this research can serve as an alternative reference for educators and future researchers in efforts to enhance students’ mathematical literacy.